2013
DOI: 10.1260/1747-9541.8.4.713
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Ball Position on Playing Space in Spanish Elite Women's Football Match-Play

Abstract: The aims of this study were to examine the playing area in female football matches according to the position of the ball. We investigated: 1) the space between the two offside lines (the length), 2) the width, 3) the distance from the least advanced defender to the goal line in defensive activity, 4) the distance from the least advanced attacker to her goal line in attacking activity, 5) the distance between the goalkeeper and her nearest attacking team mate, and 6) the distance between the goalkeeper and her … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 18 publications
1
20
0
2
Order By: Relevance
“…therefore, players must invade the space to perform a shot to goal. Similarly, previous studies reported that the distance between the defender and goal line changed depending on the ball position [13][14][15]. Additionally, our findings showed that the distance changed depending on the numerical relationship, which is important information to be taken into account in training drills.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…therefore, players must invade the space to perform a shot to goal. Similarly, previous studies reported that the distance between the defender and goal line changed depending on the ball position [13][14][15]. Additionally, our findings showed that the distance changed depending on the numerical relationship, which is important information to be taken into account in training drills.…”
Section: Discussionsupporting
confidence: 80%
“…By analysing the space control during a match, many variables have been reported, such as length (the distance between the 2 more distant players, longitudinally, without goalkeepers), width (the distance between the 2 more distant players, laterally, without goalkeepers), the area (formed by the width and length), the numerical relationship (the number of attacking players vs. the number of defending players inside a given area), and individual playing area (IPA) (obtained by dividing the area among the players) [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tais disputas aumentam a quantidade de contatos físicos, o que pode levar a uma maior ocorrência de faltas e perdas de bola pela linha lateral. Tais inferências estão de acordo com os achados de Zubillaga et al (2013). Eles demonstraram que quando a bola se encontrava nos setores de meio campo, o comprimento do espaço de jogo efetivo diminuía significativamente.…”
Section: Discussionunclassified
“…The influence of the zone of the pitch as a performance indicator (Reina Gómez & Hernández-Mendo, 2012) was previously analysed in relation to the areas for game situations Zubillaga et al, 2013). Different zones of the pitch depending on the tactical aims and the phases of the game can be considered to show a practical justification of the results of this study (Garganta, 1997;Díaz-Díaz, 2011) During a soccer match, numerous situations and actions directly involve the nearest players to the player in possession of the ball.…”
Section: Introductionmentioning
confidence: 99%